Respuesta :

xy = -48
x + y = 2

[tex]xy = -48[/tex]
[tex]\frac{xy}{x} = \frac{-48}{x}[/tex]
[tex]y = \frac{-48}{x}[/tex]

[tex]x + y = 2[/tex]
[tex]x + \frac{-48}{x} = 2[/tex]
[tex]\frac{x^{2}}{x} + \frac{-48}{x} = 2[/tex]
[tex]\frac{x^{2} - 48}{x} = 2[/tex]
[tex]2x = x^{2} - 48[/tex]
[tex]0 = x^{2} - 2x - 48[/tex]
[tex]x = \frac{-(-2) \± \sqrt{(-2)^{2} - 4(1)(-48)}}{2(1)}[/tex]
[tex]x = \frac{2 \± \sqrt{4 + 192}}{2}[/tex]
[tex]x = \frac{2 \± \sqrt{196}}{2}[/tex]
[tex]x = \frac{2 \± 14}{2}[/tex]
[tex]x = \frac{1 \± 7}{1}[/tex]
[tex]x =\frac{1 + 7}{1}[/tex]    [tex]or[/tex]    [tex]x = \frac{1 - 7}{1}[/tex]
[tex]x = \frac{8}{1}[/tex]    [tex]or[/tex]    [tex]x = \frac{-6}{1}[/tex]
[tex]x = 8[/tex]    [tex]or[/tex]    [tex]x = -6[/tex]

  x + y = 2
  8 + y = 2
- 8        - 8
        y = -6
(x, y) = (8, -6)

    x + y = 2
   -6 + y = 2
 + 6       + 6
          y = 8
    (x, y) = (-6, 8)

The two numbers that multiply to -48 and add up to 2 are the numbers -6 and 8.